1999
DOI: 10.1017/s0047279499005589
|View full text |Cite
|
Sign up to set email alerts
|

A Research Evaluation of British Programmes for Violent Men

Abstract: In the last two decades there have been a number of social, medical and legal initiatives in the UK and elsewhere to provide assistance to women who suffer violence from their partner. The most recent innovations focus on responding to the men who perpetrate this violence. In this article we present the initial results of the first British study of programmes for violent men. The three-year study used a longitudinal method to compare the effects of two court mandated programmes with other, more orthodox,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
133
2
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(142 citation statements)
references
References 22 publications
3
133
2
4
Order By: Relevance
“…Much of the therapeutic writing in this field has originated in the USA (Bograd and Mederos, 1999;Goldner, 1998) and in Australia (James, 1996;Jenkins, 1990). We try to work therapeutically in line with the recommendations of the outcome research on interventions with men who physically abuse their female partners (Dobash et al, 1999;Dunford, 2000). Working in a small independent agency where our decisions and actions are exposed and without the support of a larger agency, we have responded to the challenge of needing our own policy on domestic violence, of taking responsibility within our work for reviewing and maintaining safe outcomes, and of critically reviewing our own practice with our referrers and the family members with whom we work to achieve safety in relationships.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Much of the therapeutic writing in this field has originated in the USA (Bograd and Mederos, 1999;Goldner, 1998) and in Australia (James, 1996;Jenkins, 1990). We try to work therapeutically in line with the recommendations of the outcome research on interventions with men who physically abuse their female partners (Dobash et al, 1999;Dunford, 2000). Working in a small independent agency where our decisions and actions are exposed and without the support of a larger agency, we have responded to the challenge of needing our own policy on domestic violence, of taking responsibility within our work for reviewing and maintaining safe outcomes, and of critically reviewing our own practice with our referrers and the family members with whom we work to achieve safety in relationships.…”
Section: Resultsmentioning
confidence: 99%
“…exploiting a victim's vulnerability to inflict further psychological harm. Dobash et al (1999) and Dunford (2000) comment on the inability of violent men to reflect on their violence and its consequences. In the Dobash et al evaluation study of British programmes for violent men, they noted that men who completed a programme successfully developed the ability to think about their violence and its costs to themselves, their partners, their children, and others.…”
Section: Riskmentioning
confidence: 99%
“…The first known evaluation of a UK perpetrator programs came from Dobash, Dobash, Cavanagh and Lewis (1999) who describe the introduction of perpetrator services and interventions originating as late as 1989. Their evaluation centered around two programs within Scotland (CHANGE and Lothian Domestic Violence Probation Project) which focused on the offender, his violent behavior the need for him to change.…”
Section: Perpetrator Programs In the Ukmentioning
confidence: 99%
“…Aldarando and Sugarman, 1996). Of the 60 European evaluations we reviewed, adherence and longer-tern change in motivation (Dobash et al 1999;Kavemann and Hagemann-White, 2004) or that found no difference in outcomes between those with 'internal' and 'external' motivation (e.g. Barz et al 2006).…”
Section: Who Is Participating?mentioning
confidence: 99%